Big Data Analytics for Health Care Applications Using Cloud Computing- A Study - Subhadra, K; Kavitha, N (International Journal of Computer Sciences and Engineering, 2025)
This paper focuses the art of big data in medical field general background of big data is discussed first and then its related areas, such as cloud computing, data centers, internet of things and Hadoop. The value chain four phases are discussed here that is data generation, data acquisition, data storage and data analysis. For each phase here we are introducing general background technical challenges and review the latest advantages. Big data is a concept which defines the difference between itself and “massive data” or “very big data”. Three v s of big data are volume, velocity and variety which are defined by Doung Laney in 2001